The Art of Storytelling in Bedouin Society: A 21st-Century Ethnographic Collection of Poems from the United Arab Emirates - Rainey, Elizabeth (Material Culture Review, 2015)
Abstract Individuals represent the cultural vehicles through which intangible heritage is transmitted and so this study will examine the role that Emirati oral Bedouin culture plays in this regard. Its vibrant tradition expresses emotions and teaches ethical conduct during social occasions, both a source of communal entertainment and at the same time, a lynchpin of the social hierarchy. Through diverse heritage performances, the Bedouins practise their own version of intangible culture, underscoring folk norms and informing behaviours that enforce family, tribe and country. Themes such as nature, homesickness and patriotism are examined in addition to traditional dance, as forms of patronage culture. Thus folk memory is validated and the Arabic vernacular illustrates a dynamic yet sometimes obsolete version of World Arabic. Thus the fragile nature of these resources in a rapidly developing environment is highlighted and so, too, the politics of preservation. The contributions were voluntary and the result of twenty years of social capital in the community.